Knowledge of patients with acute myocardial infarction in relation to risk factors of heart disease - Gkika, Christina; Vasilopoulos, Georgios (Health & Research Journal, 2018)
Background: Acute myocardial infarction is directly related to specific predisposing risk factors. Some of these factors, if modified in time, would probably not have led to the disease. Aim: To investigate the levels of information for patients with acute myocardial infarction in relation to predisposing factors. Methodology: For the study’s needs, a thorough review of articles in Greek and foreign-language scientific journals, in databases such as PubMed and Scopus, using the key words in Greek and in English, in all possible combinations. Results: According to literature it appears that only a small percentage of patients have a good level of knowledge about the predisposing factors of the disease. Also, the good level of knowledge is directly related to the male gender and the highest level of education. Focusing on patients with Acute Myocardial Infarction is lacking a good level of knowledge, but in a smaller percentage than other cardiac patients. The implementation of aggressive educational strategies aimed at informing the population is the main way to tackle the growing incidence of the disease. In this educational process, medical and nursing staff play a key role, which should be encouraged to educate patients about the onset and progression of disease, predisposing factors and prevention measures when providing health services. Conclusions: There are not enough studies in the literature to estimate the knowledge of patients with acute myocardial infarction on predisposing factors. New studies should therefore be carried out with a view to providing a more detailed picture of the level of knowledge, as the depiction of knowledge will contribute